Adaptive Wall-Based Attachment Ventilation: A Comparative Study on Its Effectiveness in Airborne Infection Isolation Rooms with Negative Pressure. (January 2022) - Zhang, Ying; Han, Ou; Li, Angui; Hou, Li'an; Olofsson, Thomas; Zhang, Linhua; Lei, Wenjun
Abstract: The transmission of coronavirus disease 2019 (COVID-19) has presented challenges for the control of the indoor environment of isolation wards. Scientific air distribution design and operation management are crucial to ensure the environmental safety of medical staff. This paper proposes the application of adaptive wall-based attachment ventilation and evaluates this air supply mode based on contaminants dispersion, removal efficiency, thermal comfort, and operating expense. Adaptive wall-based attachment ventilation provides a direct supply of fresh air to the occupied zone. In comparison with a ceiling air supply or upper sidewall air supply, adaptive wall-based attachment ventilation results in a 15%–47% lower average concentration of contaminants, for a continual release of contaminants at the same air changes per hour (ACH; 10 h −1 ). The contaminant removal efficiency of complete mixing ventilation cannot exceed 1. For adaptive wall-based attachment ventilation, the contaminant removal efficiency is an exponential function of the ACH. Compared with the ceiling air supply mode or upper sidewall air supply mode, adaptive wall-based attachment ventilation achieves a similar thermal comfort level (predicted mean vote (PMV) of −0.1–0.4; draught rate of 2.5%–6.7%) and a similar performance in removing contaminants, but has a lower ACH and uses less energy.